ANALISIS KUALITAS DAN KEBUTUHAN AIR MASYARAKAT DUSUN BLOKAGUNG DESA KARANGDORO BANYUWANGI - Putu Aryastana; I Gusti Agung Putu Eryani; Cok Agung Yujana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
Water is a requirements for all humanity. Banjar Kiadan is one of the hamlets located in Pelaga Village, Petang Sub-district, Badung Regency witness raw water problem, so it is necessary to analyze the requirements of water needs. The analysis of raw water supply needs includes: water demand analysis for the next 25 years, analysis of water supply system planning, and analysis of budged plan of water supply system. The source of water that can be utilized is â€œPeninjauan Springâ€ with discharge 1.85 lt/sec. Total water demand is calculated based on the number of water users to be projected for the next 25 years. The water requirement is calculated based on 2 (two) scenario plan of the network that is if built SR (Home Connection) or just made KU (Public Faucet). The results showed that the total water requirement in 2042 was 2.264 lt/sec for the assumption of using home connection, while for the assumption using the public faucet was 0.903 lt/sec. The water supply system used is a gravity system with a public faucet as a distribution system. The budget plan for the water supply system is IDR.3,386,655,000.00.